1999
DOI: 10.1034/j.1600-051x.1999.261005.x
|View full text |Cite
|
Sign up to set email alerts
|

The barrier between the keratinized mucosa and the dental implant

Abstract: The present study was performed in order to examine the composition of the connective tissue that forms an attachment to a dental implant. 6 beagle dogs were used. All mandibular premolars were extracted. After 3 months of healing, 6 fixtures--3 in each side of the mandible--(Astra Tech Implants, Dental System TiO blast; Astra Tech AB, Mölndal, Sweden) were installed. After another 3 months of healing, abutment (Uni-abutment 45; Astra Tech AB, Mölndal, Sweden) connection was performed and a plaque control prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
25

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 10 publications
7
139
0
25
Order By: Relevance
“…32% of the HGFs of all components. They concluded that HGFs help maintain the seal between soft tissue and implant abutments (9).…”
Section: Introductionmentioning
confidence: 99%
“…32% of the HGFs of all components. They concluded that HGFs help maintain the seal between soft tissue and implant abutments (9).…”
Section: Introductionmentioning
confidence: 99%
“…In a beagle dog study of crystal sapphire implants that were placed in one-stage procedure Fartash et al (Fartash et al, 1990) observed discrete inflammatory infiltrate in periimplant soft tissue, while Chavrier et al (Chavrier et al, 1994, as cited in Weber & Cochran, 1998 observed inflammatory cells in approximately half the biopsies in their study on experimental dogs. Buser et al (Buser at al., 1990) detected the presence of periimplant epithelial attachment in one-stage implants in experimental dogs, while Abrahmsson et al (Abrahamsson et al, 1996(Abrahamsson et al, , 1999 in their similar experimental studies reported that surgical method had not influence on the formation and structure of periimplant soft tissue. Weber et al comparing non-submerged and submerged implants in beagle dogs, found significant differences between implant types.…”
Section: Studies On Periimplant Soft Tissuementioning
confidence: 99%
“…Numerous reports have compared the submerged and non-submerged implant types in animal models (Ericsson et al, 1996;Weber et al, 1996;Abrahamsson et al, 1996Abrahamsson et al, , 1999Levy et al, 1996;Fiorellini et al, 1999;Moon et al, 1999;Berglundh et al, 2007). The amount of scientific work was focused on the achieving and maintaining a healthy relationship of dental implants to the surrounding hard and soft tissues over extended periods.…”
Section: Experimental Researchmentioning
confidence: 99%
“…Histological analysis of in vivo models, including animal and human subjects, is one of the gold standard methods for investigating the mechanisms at the implant-soft tissue interface. However data on periimplant tissue from human subjects are scarce because of the limited collecting opportunities and ethical issues (Piattelli et al, 1993(Piattelli et al, , 1997a(Piattelli et al, , 1997bArvidson et al, 1996;Corpe et al, 1999;Baschong et al, 2001), animal models have therefore been widely used (Albrektsson et al, 1985;Buser et al, 1992;Berglundh et al, 1994;Berglundh & Lindhe, 1996;Weber et al, 1996;Abrahamsson et al, 1998, Fujii et al, 1998, 2003Kawahara et al, 1998;Moon et al, 1999;Hermann et al, 2000Hermann et al, , 2001. Peri-implant tissue contains both hard (bone) and soft (mucosa) tissues, which presents a challenge in terms of the histochemical examination of the intact implant-soft tissue interface.…”
Section: Implant Dentistry -The Most Promising Discipline Of Dentistrmentioning
confidence: 99%